A Study on the method comparison of rice sample preparation for inorganic arsenic analysis - สินะวิวัฒน์ สวรินทร์; เมธียนต์พิริยะ นงนุช (Bulletin of Applied Sciences, 2022)
The aim of this research is to compare the sample preparation for inorganic arsenic analysis in rice. The measurement of inorganic arsenic in rice using speciation technique with high performance liquid chromatography coupled to inductively plasma mass spectrometry (HPLC-ICP-MS) is described. Arsenic species were separated and determined by chromatographing extracts on ion exchange column with ammonium phosphate buffer as the mobile phase at a pH 6.3. Jasmine rice was extracted by 2 methods, treatment with Trifluoroacetic acid (TFA) and solvent extraction with sonication. The study showed that the sample treatment by solvent extraction with sonication gave the better accuracy than the sample treatment with TFA. It may be resulted from the interference on inorganic arsenic (as As(V)) chromatogram in the sample treatment with TFA. Then the preliminary study for total arsenic and inorganic arsenic in rice was done by using the samples prepared from solvent extraction with sonication method. The results showed that the total arsenic in jasmine rice samples ranged from 0.072 to 0.075 mg/kg whereas the inorganic arsenic ranged from 0.032 to 0.039 mg/kg.